2013
DOI: 10.3109/02813432.2012.751699
|View full text |Cite
|
Sign up to set email alerts
|

A Quick Test of Cognitive Speed (AQT): Usefulness in dementia evaluations in primary care

Abstract: Our results suggest AQT is a usable test for dementia assessments in primary care. Sensitivity for AQT is superior to CDT, equivalent to MMSE, and comparable to the combination MMSE and CDT. MMSE in combination with AQT improves sensitivity. Because AQT is user-friendly and quickly administered, it could be applicable for primary care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…The ideal cognitive screening test for primary care would be brief, easily administrable, and scored with high sensitivity and specificity for identifying impairment (Milne et al, 2008;Holsinger et al, 2012). So it has been suggested that AQT could replace CDT in combination with MMSE for dementia evaluation (Kvitting et al, 2013). Alas, the CDT has proved to be difficult to assess in the primary care setting (Ehreke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal cognitive screening test for primary care would be brief, easily administrable, and scored with high sensitivity and specificity for identifying impairment (Milne et al, 2008;Holsinger et al, 2012). So it has been suggested that AQT could replace CDT in combination with MMSE for dementia evaluation (Kvitting et al, 2013). Alas, the CDT has proved to be difficult to assess in the primary care setting (Ehreke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Parts one and two are measures of perceptual speed, whereas part three is a measure of cognitive speed, including set shifting, attention, and working memory. AQT has proven reliability and validity for the detection of early dementia [30][31][32], and is used as a routine cognitive screening test in southern Sweden. In line with the most other studies including AQT testing, only data from AQT part three were analysed in the present study.…”
Section: Cognitive Testsmentioning
confidence: 99%
“…Traditional cognitive status scales show little sensitivity in distinguishing between the normal range of cognitive function and cognitive impairments [7] and are in uenced by culture, language, and education [9]. The Mini-Mental State Examination (MMSE) and the Clock Drawing Test (CDT) are diagnostic tests for dementia, whose accuracy is still questionable, and which limits the ability to diagnose patients with early-stage dementia and MCI [10]. In contrast, the use of visual-verbal scales such as A Quick Test of Cognitive Speed (AQT) that are not in uenced by factors such as gender, formal education beyond the acquisition of literacy (Grades 5 to 8), and culture, can distinguish between normal aging and cognitive disorders caused by disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…AQT measures the speed of perception, retrieval, and naming of basic colors and forms in singledimension naming and cognitive speed associated with central executive functions (attention, working memory, and set shifting) in dual-dimension naming of color-form combinations. Studies showed that a decline in the speed of perception and cognition precedes a decline in linguistic-cognitive abilities in mild to moderate severity of AD [10].…”
Section: Introductionmentioning
confidence: 99%